In Search of School’s Sausative Power. Review of Research and Effective School Models - Nowosad, Inetta; Łukasik, Joanna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2020)
The article has a format of a review. As such, it focuses on previous research and proposals for effective school models developed on its basis. It has been recognised that the category of school effectiveness is hardly present in Polish pedagogy, and its implications for research and improvement of school work are significant. Therefore, familiarisation with global achievements in this area is deemed valuable as a motivational and inspirational factor for scientific research among pedagogues who deal with school issues. For this purpose, a critical review of selected effective school models, which are important in the development of educational research focused on improving both the school and the school system, was carried out. The article justifies the change of approach that has been introduced into this area, as well as delineates perspectives for further research and exploration.